ANALYZE BRAND EQUITY AND COMPETITIVE ADVANTAGE ON MARKETING PERFORMANCE - Ramdan Nurul Anwar; R. Deni Muhammad Danial; Kokom Komariah (Inovbiz: Jurnal Inovasi Bisnis, 2022)
The purpose of this study is to analyze brand equity and competitive advantage on marketing performance. The method used in this research is descriptive method and associative method with a quantitative approach. The type of sampling technique used in this study is using a non-probability sampling approach. The data analysis technique used is multiple linear regression analysis, including the coefficient of determination test, multiple correlation coefficient, and partial test (T test). The results of the study, using the coefficient of determination test seen from the value (Adjusted R2) of 0.619, this means that the influence of brand equity and competitive advantage on marketing performance is 61.9%, the remaining 38.1% is influenced by other factors not explained in this study. . From the results of the correlation coefficient test, it can be seen that the R value of 0.787 indicates a strong relationship between brand equity and competitive advantage on marketing performance.